Haunting at Home Plate - Patneaude, David (Morton Grove, Ill. : A. Whitman, 2000)
After they hear stories about their baseball field being haunted by the ghost of a boy who died there many years ago, twelve-year-old Nelson and his teammates start finding mysterious messages written in the dirt.
Keywords: Baseball -- Fiction; Ghosts -- Fiction